Gambaran Status Gizi, Anemia, dan Usia Menarche Pada Siswi SDIT Smart Insani Yukum Jaya, Lampung Tengah Tahun 2025 - Kurniawati, Dewi; S, Supriyanti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Nutritional status, anemia, and age at menarche are important indicators in assessing the health and development of adolescent girls. Proper nutrition and adequate hemoglobin levels play a crucial role in ensuring that menarche occurs at a normal age. Anemia in adolescent girls can affect physical and cognitive development and increase future health risks. This study aims to describe the nutritional status, anemia status, and age at menarche among female students at SDIT Smart Insani Yukum Jaya, Central Lampung Regency, in 2025. This research employs a descriptive design with a quantitative approach. The study sample consists of female students who have experienced menarche, selected through purposive sampling. Data were collected through body mass index (BMI) measurements for nutritional status, hemoglobin level tests for anemia, and interviews regarding age at menarche. Data analysis was conducted descriptively in the form of frequency distribution and percentages. The results show that most respondents have a normal nutritional status, although some students exhibit undernutrition and overnutrition. Additionally, the prevalence of anemia among students who have experienced menarche is relatively significant, with hemoglobin levels below the normal threshold. The age at menarche varies, with the average age still within the normal range, although some cases of early or delayed menarche were observed. Nutritional status and anemia influence the age at menarche among students at SDIT Smart Insani Yukum Jaya. Better nutritional interventions and anemia prevention programs are needed to improve adolescent girls' health.